Genomic and clinical characterization of pediatric lymphoepithelioma-like carcinoma - Yi Que; Xiuxia Lu; Suying Lu; Feifei Sun; Jia Zhu; Yu Zhang; Juan Wang; Junting Huang; Wei Liu; Fenghua Wang; Liping Li; Li Zhang; et al. (Journal of Translational Medicine)
Abstract Background Pediatric lymphoepithelioma-like carcinoma (pLELC) is a rare neoplasm with unclear prognosis, genome, and tumor microenvironment. Our study aims to elucidate its genomic and clinical characteristics. Methods Forty-one pLELC patients were enrolled at Sun Yat-sen University Cancer Center from 2012 to 2023. Kaplan–Meier analysis was utilized to estimate progression-free survival (PFS) and overall survival (OS). Baseline plasma protein levels from 16 patients and 9 health controls were analyzed using a Olink proteomic platform and whole exon sequence (WES) was performed on 11 tumor samples from 10 pediatric patients. Immunohistochemistry (IHC) for PD-L1was performed, and the infiltration of CD4+ or CD8+ T cells was evaluated. Results Patients receiving anti PD-1 in combination with chemotherapy had a 1-year PFS of 100%, while the 2-year PFS was 72.92% (95%CI: 46.80‒100%). The 1-year OS for patients receiving anti PD-1 in combination with chemotherapy was 100%, and the 2-year OS was 87.5% (95%CI: 67.34–100%). Significant upregulation of immune checkpoint molecules was detected including LAG-3, PD-L1, and galectin-9 in LELC group by proteomic analysis (P < 0.05). The mutational landscape of pediatric LELC presented more genes mutated in pathways associated with immune, DNA repair, cell cycle and NOTCH. Pathway analysis of mutational profiles indicated DNA repair pathway and SWI/SNF complex were potential drug targets for pLELC patients. All the pediatric LELC patients evaluated exhibited positive PD-L1 expression and CD4+/CD8+ T cells infiltration. Conclusions Our findings indicate a promising response rate associated with the combination of PD-1 antibody treatment and chemotherapy in pediatric patients with LELC, providing a theoretical basis for targeting DNA repair pathways. These outcomes suggest that clinical trials involving immune checkpoint inhibitors are warranted in pediatric patients with LELC.